Constructing an information science resource ontology based on the Chinese Social Science Citation Index. Issue 2 (10th March 2014) - Qiu, Junping; Lou, Wen
Abstract : Purpose: – The purpose of this study is to construct a Chinese information science resource ontology and to explore a new method for semiautomatic ontology construction. Design/methodology/approach: – More than 8, 290 articles indexed in the Chinese Social Science Citation Index (CSSCI), covering the years 2001 to 2010, were included in this study. Statistical analysis, co-occurrence analysis, and semantic similarity methods were applied to the selected articles. The ontology was built using existing construction principles and methods, as well as categories and hierarchy definitions based on CSSCI indexing fields. Findings: – Seven categories were found to be relevant for the Chinese information science resource ontology, which, in this study, consists of a three-tier architecture, 78, 291 instances, and 182, 109 pairs of semantic relations. These results indicate the following: further improvements are required in ontology construction methods; resource ontology is a breakthrough concept in ontology studies; the combination of semantic similarities and co-occurrence analysis can quantitatively describe relationships between concepts. Originality/value: – This study pioneers the resource ontology concept. It is one of the first to combine informetric methods with semantic similarity to reveal deep relationships in textual data.